ANALYSIS OF NURSING CARE FOR THE ELDERLY USING THE IMPLEMENTATION OF VIRGIN COCONUT OIL (VCO) TO OVERCOME SKIN INTEGRITY DISORDER IN DERMATITIS AT THE JAMBANGAN WREDA NURSING HOME, SURABAYA - Anggraini, Dewi Puspita; Zahroh, Chilyatiz; Noventi, Iis; Setiyowati, Eppy (Nurse and Holistic Care, 2024)
Introduction: Dermatitis can disrupt skin integrity, with sufferers feeling itchy, damage to the skin layer, and decreased skin elasticity causing the skin to become dry and scaly. Objective: This study aims to provide nursing care by administering virgin coconut oil (VCO) to elderly people suffering from dermatitis to overcome skin integrity disorders at the Surabaya Nursing Home. Methods: The research method used is a case study. The subject of this research is Mrs. T is 77 years old with problems with skin integrity disorders and was given virgin coconut oil (VCO). The assessment was conducted through interviews and direct observation of the patient using a gerontic nursing care sheet and applying VCO according to the SOP. Results: The results obtained in this study were, after 5 days of intervention, giving virgin coconut oil (VCO) 2x a day, the results were obtained with reduced itching, and elasticity from scale 2 (quite decreased) to scale 5 (increased) as evidenced by visible skin. Quite moist which was initially dry and scaly, tissue damage from scale 2 (quite increased) to scale 5 (decreased) it was proven that inflammation around the skin area decreased which initially had a red rash, damage to the skin layer from scale 2 (quite increased) to scale 5 (decreased) results showed that the reddish rash on the skin decreased, the blackened wound spots decreased. Conclusions: The use of virgin coconut oil reduces itching, increases skin elasticity, reduces tissue damage, and reduces damage to the skin layer.